Knowledge, attitudes and practice toward cervical cancer screening among Sikkimese nursing staff in India - Hafizur Rahman; Sumit Kar (Indian Journal of Medical and Paediatric Oncology)
Objectives: To assess baseline knowledge of cancer cervix, screening and practice of Pap smear screening among Sikkimese staff nurses in India. Materials and Methods: Between April 2012 and February 2013, a predesigned, pretested, self -administered multiple responses questionnaire survey was conducted among staff nurses′ working in various hospitals of Sikkim. Questionnaire contained information about their demographics, knowledge of cervical cancer, its risk factors, screening methods, attitudes toward cervical cancer screening and practice of Pap smear amongst themselves. Results: Overall, 90.4% nurses responded that they were aware of cancer cervix. Three quarter of the staff nurses were not aware of commonest site being cancer cervix in women. Of the 320 participants, who had heard of cancer cervix, 253 (79.1%) were aware of cancer cervix screening. Pap smear screening should start at 21 years or 3 years after sexual debut was known to only one-third of the nursing staff. Age was found to be a significant predictor of awareness of Pap smear screening among nursing staff. Awareness was significantly more prevalent among older staff (P < 0.007). Married nursing staffs were significantly more likely to be aware of screening methods, and nursing staff of Christian and Buddhist religion were 1.25 times and 2.03 times more likely to aware of screening methods than Hindu religion respectively. Only 16.6% nurses, who were aware of a Pap smear (11.9% of the total sample), had ever undergone a Pap smear test. Most common reason offered for not undergoing Pap smear test were, they felt they were not at risk (41%), uncomfortable pelvic examination (25%) and fear of a bad result (16.6%). Conclusion: Knowledge of cancer cervix, screening and practice of Pap smear was low among Sikkimese nursing staff in India. There is an urgent need for re-orientation course for working nurses and integration of cervical cancer prevention issues in the nurses′ existing curriculum in India and other developing countries.